(untitled) (Asian Journal of Social Science Studies, 2022)
Compared with Mozart whose deeply influenced by J.S Bach‟s music interpreted the characteristics of music, as “men serve god”. Except for the strong religious elements, both Haydn and Mozart had experiences employed as court musicians making their music more ingratiate the royalties which is so much different from Beethoven‟s music realism. “Every rational person can advance society, and a person of genius can unhinge the world.” Fully expressed the enlightenment elements in his music, especially after the French revolution.